Water stress as a critical issue for Mediterranean viticulture: economic evidence from the Montepulciano d’Abruzzo PDO grape based on a case study in central Italy - Deborah Bentivoglio; Giulia Chiaraluce; Adele Finco (Wine Economics and Policy, 2024)
Climate change has impacted viticulture in almost all of the Mediterranean area, mainly because of temperature rises and changes in precipitation patterns, thus influencing yield, quality, and the management of grape production. One of the measures to mitigate these effects is the adoption of irrigation strategies. This has environmental and economic implications. Thus, it seems essential to evaluate if irrigation is economically and environmentally justified to ensure the sustainability of the vineyard by preserving the water resource. The aim of this research is to compute water-use indicators such as Water Productivity and Economic Water Productivity using field data obtained and to assess the economic impact of supplemental irrigation expenses through the analysis of a single case study. Since the results are heavily influenced by pedoclimatic conditions, vineyard structure, and economic decisions, the generalizability of our findings is not conceivable. However, our findings are valuable in determining when supplemental irrigation is or is not viable. Nonetheless, the findings might shed light on how water is managed in an Italian vineyard. Future supplemental irrigation plans ought to be developed using precision viticulture technologies to monitor the intricate soil-plant-environment system.